2017
DOI: 10.5812/aapm.57810
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Effect of Promethazine/Dexamethasone and Metoclopramide /Dexamethasone on Postoperative Nausea and Vomiting after Laparascopic Gastric Placation: A Randomized Clinical Trial

Abstract: BackgroundLaparoscopic gastric plication (LGP) is a technique in the restrictive category of bariatric procedures that reduces the gastric volume and increases intragastric pressure. Nausea and vomiting are the most common complications after this procedure. The goal of this research is to compare the combined effect of promethazine/dexamethasone versus Metoclopramide/ dexamethasone on the prevention of nausea and vomiting after LGP.MethodsIn recovery, the patients were divided into two groups, the Metoclopram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Postoperative nausea and vomiting (PONV) is defined as a postoperative gastrointestinal dysfunction, with mild PONV documented to have a negative impact on nutritional intake and comfort, and severe PONV leading to water-electrolyte disturbances, wound rupture, aspiration risk, and aspiration pneumonia [ 1 ]. It has a certain detrimental effect on postoperative recovery, and further takes a toll on patients' health and medical expenditure [ 2 ]. The incidence of PONVs induced by various surgeries is estimated to be 15%–46.1% [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative nausea and vomiting (PONV) is defined as a postoperative gastrointestinal dysfunction, with mild PONV documented to have a negative impact on nutritional intake and comfort, and severe PONV leading to water-electrolyte disturbances, wound rupture, aspiration risk, and aspiration pneumonia [ 1 ]. It has a certain detrimental effect on postoperative recovery, and further takes a toll on patients' health and medical expenditure [ 2 ]. The incidence of PONVs induced by various surgeries is estimated to be 15%–46.1% [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metoclopramide belongs to the group of medications known as dopamine-receptor antagonists and is widely used as an antiemetic. However, metoclopramide alone is used as an antiemetic for PONV prophylaxis [12], but it is seems that several clinicians use it as a rescue antiemetic [13]. Interestingly, although these two drugs alone are well known, the combination of the two has been less commonly used in PONV after bariatric surgery (see Appendix).…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al proposed that prophylactic administration of 2.5-5 mg dexamethasone can reduce the frequency of PONV, lower visual analog pain scores, facilitate recovery to home readiness, and improve satisfaction in outpatients undergoing anorectal surgery [17]. Talebpour et al concluded that dexamethasone-promethazine was more effective in reducing PONV and pain than metoclopramidepromethazine combination in patient undergoing laparoscopic gastric placation [18]. Ahsan et al found a combination of ondansetron with dexamethasone more efficacious than ondansetron alone in preventing PONV after laparoscopic cholecystectomy [19].…”
Section: Discussionmentioning
confidence: 99%